The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fpsyg.2014.01162
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and psychophysiological investigation of the link between anxiety, enhanced affective reactivity and interoception in people with joint hypermobility

Abstract: Objective: Anxiety is associated with increased physiological reactivity and also increased “interoceptive” sensitivity to such changes in internal bodily arousal. Joint hypermobility, an expression of a common variation in the connective tissue protein collagen, is increasingly recognized as a risk factor to anxiety and related disorders. This study explored the link between anxiety, interoceptive sensitivity and hypermobility in a sub-clinical population using neuroimaging and psychophysiological evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 37 publications
10
63
1
Order By: Relevance
“…Respondents rate each item on a six‐point scale ranging from 0 ( never ) to 5 ( always ), with lower scores reflecting greater interoception deficits. Strong evidence of the MAIA's convergent and discriminant validity and adequate‐to‐strong reliability has been demonstrated in previous research (Mallorquí‐Bagué et al., ; Mehling et al., ).…”
Section: Methodssupporting
confidence: 60%
“…Respondents rate each item on a six‐point scale ranging from 0 ( never ) to 5 ( always ), with lower scores reflecting greater interoception deficits. Strong evidence of the MAIA's convergent and discriminant validity and adequate‐to‐strong reliability has been demonstrated in previous research (Mallorquí‐Bagué et al., ; Mehling et al., ).…”
Section: Methodssupporting
confidence: 60%
“…Celletti et al [] observed that patients with a JHS/hEDS had high scores of kinesiophobia. JHS/hEDS patients also have hyperalgesia [Castori, ], enhanced interoception [Mallorqui‐Bague et al, ; Bulbena et al, ], and a tendency toward a somatosensory amplification [Baeza‐Velasco et al, ]. These aspects related to increased perception and/or reduced tolerance of pain [Feuerstein and Beattie, ; Pollatos et al, ], might influence the pain experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importantly, interoceptive awareness is ambiguous and can be associated with both deleterious and beneficial effects [5,8]. Maladaptive forms of IA characterized by hypervigilance and catastrophizing over body sensations are linked with clinical complaints, such as chronic pain [12], anxiety [13,14] and disordered eating [15]. However, healthy forms of IA characterized by appropriate attention regulation and acceptance can also be used to disengage from maladaptive thoughts and improve clinical symptoms, such as with pain and depression [16,17].…”
Section: Interoceptive Awareness and Psychological Well-beingmentioning
confidence: 99%